Litopenaeus vannamei peroxiredoxin 2-like is involved in WSSV infection by interaction with wsv089 and VP26. (January 2022) - Ren, Xing-Chao; Liu, Xiao-Ping; Liu, Qing-Hui
Abstract: White spot syndrome virus (WSSV) is one of the most dangerous pathogen in shrimp aquaculture, which can cause extremely high mortality of shrimp. A full understanding of virus-host interactions is important to prevent viral infection. In the present study, wsv089-interacting molecule Litopenaeus vannamei peroxiredoxins2-like ( LvPrx2-L ) was selected by the yeast two-hybrid (Y2H) method. The interaction between wsv089 and LvPrx2-L was confirmed by far-western blotting assay. Interestingly, a further study indicated that LvPrx2-L interacted with VP26, and the molecular docking analysis supported the interaction between LvPrx2-L and VP26. Tissues distribution assay showed that LvPrx2-L was detected in all sampled tissues. The highest expression of LvPrx2-L was appeared in hemocytes. Following WSSV challenge, LvPrx2-L mRNA transcripts were significantly increased in the hemocytes and gill. In addition, the relative expression of IE1 and VP28 were remarkably up-regulated in the hepatopancreas and intestines of LvPrx2-L -knockdown shrimp. Moreover, the cumulative survival rate was significantly lower in the LvPrx2-L- silenced group compared with the control and blank groups. Furthermore, LvPrx2-L could regulate the expression of proPO, crustin, ALF3, and CAT at the mRNA level. These findings would further deepen our understanding of WSSV-host interaction and shrimp antiviral response. All these data might useful for assessing the function of LvPrx2-L in the immune response of crustacean. Highlights: wsv089 and VP26 interacts with LvPrx2-L. LvPrx2-L mRNA transcripts were significantly increased after WSSV challenge. IE1 and VP28 were remarkably up-regulated in LvPrx2-L knockdown shrimp. The cumulative survival rate was significantly lower in LvPrx2-L silenced group. LvPrx2-L regulate the mRNA expression of proPO, crustin, ALF3 and CAT.